2023
DOI: 10.3390/molecules28093913
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyrimidine Derivatives as Antioxidant and Anticancer Agents: Design, Synthesis and Molecular Modeling Studies

Malama Myriagkou,
Evangelia Papakonstantinou,
Georgia-Eirini Deligiannidou
et al.

Abstract: The heterocyclic ring system of pyrido [2,3-d]pyrimidines is a privileged scaffold in medicinal chemistry, possessing several biological activities. The synthesis of the pyrimidine derivatives was performed via the condensation of a suitable α,β-unsaturated ketone with 4-amino-6-hydroxy-2-mercaptopyrimidine monohydrate in glacial acetic acid. Chalcones were synthesized, as starting materials, via the Claisen–Schmidt condensation of an appropriately substituted ketone and an appropriately substituted aldehyde i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The absorbance was recorded at 517 nm after 20 and 60 min at room temperature ( Table 2 ). The test follows our previous published methods [ 31 , 73 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance was recorded at 517 nm after 20 and 60 min at room temperature ( Table 2 ). The test follows our previous published methods [ 31 , 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…A considerable number of clinically used drugs such as minoxidil, phenobarbital, primidone, zidovudine, stavudine, 5-flurouracil, methotrexate, imatinib, dasatinib, pazopanib, nilotinib, cytarabine, uramustine, tegafur, risperidone, sulfamethazine and trimethoprim contain the pyrimidine heterocyclic scaffold [ 14 , 15 ]. In recent years, diverse biological activities of pyrimidine derivatives, including anticancer [ 16 , 17 ], antibacterial [ 18 , 19 , 20 ], antifungal [ 21 ], antitubercular [ 21 , 22 ], antimalarial [ 23 ], antiviral [ 24 , 25 , 26 ], analgesic [ 27 ], antioxidant [ 28 , 29 ], anti-lipoxygenase [ 30 , 31 ] and anti-inflammatory activities have been reported [ 32 , 33 ]. Thus, the pyrimidine ring can be considered as a promising pharmacophoric scaffold for the synthesis of novel bioactive molecules for the treatment of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pontiki's group observed that some pyrimidine compounds showed limited interaction with DPPH but exhibited significant inhibition of lipid peroxidation (Figure 21) [101]. In this study, samples (e.g., compound 71) were tested using AAPH (2,2 0 -Azobis(2-methylpropionamidine) dihydrochloride) to generate peroxy radicals, with sodium linoleate undergoing peroxidation.…”
Section: Pyrimidine Compounds Exhibiting Antioxidant Activitiesmentioning
confidence: 97%
“…Analogues based on pyrimidine and its annulated heterocyclic compounds have garnered significant interest due to their diverse biological properties, including antimicrobial [1][2][3], anti-inflammatory [4,5], antioxidant [6,7], antiviral [8], and antitumour [9][10][11][12] effectiveness.…”
Section: Introductionmentioning
confidence: 99%